THE POTENTIAL OF VEGETATION DENSITY, VEGETATION HEALTH, CHLOROPHYLL, AND NITROGEN ON THE SURVIVAL OF BEKANTAN (CASE STUDY: BAKUT ISLAND, ANJIR MUARA DISTRICT, BARITO KUALA REGENCY, SOUTH KALIMANTAN PROVINCE) - Nazara, Ezer Ayusalin; Puspita, Elza Nadia; Aristin, Nevy Farista; Muhaimin, Muhammad (International Conference On Social Science Education, 2023)
Ecosystem imbalance results in the disruption of the bekantans survival as one of the endemic animals in Kalimantan. Bakut Island has become one of the natural tourist parks that serves as a place to protect and preserve the bekantan’s survival. bekantans will be protected when their environmental potential is sufficient and capable of providing their food needs, a habitat for their dwelling, and avoiding wild hunting. The purpose of this research is to assess the potential vegetation density, vegetation health, chlorophyll content, and nitrogen content on Bakut Island as a supporter of the bekantan's ecosystem. The research method involves calculating vegetation density index, vegetation health, chlorophyll, and nitrogen using the NDVI, NDRE, CI Green, and NDNI formulas. The research results showed a vegetation density index of 0,4 (very high), vegetation health of 0,32 (very high), chlorophyll content of 1,23 (very high), and nitrogen content of 0,11 (very high). Bakut Island has very high potential as a supporter of the bekantan's ecosystem for sustainability and survival. This is because Bakut Island's ecosystem has an abundance of food, good vegetation health, and a supportive habitat for reproduction. Therefore, this research implies a guideline for maintaining vegetation and habitat consistency to preserve the survival of Bekantans as endemic animals in Kalimantan.